PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SEKTOR PERTANIAN DI ACEH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI ACEH - Triara Juniarsih (VALUE, 2021)
GRDP is a measuring tool to determine the government's success or failure in utilizing existing resources and as a reference in planning and decision-making. This study aimed to assess the GRDP of the Agricultural Sector in Aceh on the GRDP of Aceh Province and find out which agricultural subsectors affect the GRDP of the Agricultural Sector. The data collection method is done by collecting secondary data in Time Series data or periodic data from year to year, namely from 1996-2010. The analytical method used is multiple linear regression analysis. The research results show that for every increase in the GRDP of the agricultural sector by one billion rupiahs, the GRDP Aceh will increase by 1.919 billion rupiahs. The coefficient of determination (R2) is 0.885, which means that the variety of explanatory variables can explain the dependent variable by 88.5%. Variations in changes in GRDP are influenced by the agricultural, industrial, and service sectors, while the remaining 11.5% are influenced by other sectors outside the farming, industrial, and service sectors. Based on the regression analysis results on the Aceh GRDP equation, it can be concluded partially that the GRDP of the agricultural industry, GRDP of the processing industry sector, and GRDP of the service sector have a significant effect on GRDP Aceh. The sub-sector that provides the enormous contribution and affects the GRDP of the agricultural industry with a forestry coefficient of 1.024, which means that every one billion rupiah increase in forestry will increase the GRDP of the farm sector to 1.024 billion rupiahs, where the coefficient of determination (R2) is 1.00. that means that independent variables' diversity can explain the dependent variable by 100%, influenced by the Tabama, Plantation, Animal Husbandry, Forestry, and Fisheries sub-sectors. The increase in GRDP in the agricultural sector can increase the GRDP of Aceh Province. And of all the farm sub-sector, the forestry sub-sector gave the most considerable contribution to improving the GRDP of the agricultural sector in Aceh.